Exploring Educational Philosophy of Primary School Teacher Candidates in Turkey - Zeynel Amac; Behçet Oral (Dinamika Ilmu, 2023)
Every teacher has a philosophy that affects their education practices and approaches to students. The adopted educational philosophy guides the teachers who are the implementers of the curriculum. Therefore, it is crucial to explore the educational philosophy adopted by teacher candidates, who are expected to be good curriculum practitioners and be educated in this direction. This qualitative study explored primary school teacher candidates’ philosophy of education. Data were collected from 24 primary school teacher candidates and analyzed thematically. The results showed that the participants mostly held the philosophy of Progressivism, and some had an eclectic understanding. Because Turkey's current primary school curriculum was prepared according to the philosophy of Progressivism, it can be inferred that teacher candidates who believe in this philosophy are compatible with the curriculum. It is also concluded that teacher candidates with a philosophy other than Progressivism have not yet fully understood the curriculum. Activities related to increasing knowledge and awareness about educational philosophies in teacher education programs are recommended.